Response of soil nutrients to terracing and environmental factors in the Loess Plateau of China - Die Chen; Wei Wei; Liding Chen; Bojun Ma; Hao Li (Geography and Sustainability, 2024)
Terracing is a widely adopted agricultural practice in mountainous regions around the world that aims to conserve soil and water resources. Soil nutrients play a crucial role in determining soil quality, particularly in landscapes prone to drought. They are influenced by factors such as land-use type, slope aspect, and altitude. In this study, we sought to examine the impact of terracing on soil nutrients (soil organic content (SOC), total nitrogen (TN), nitrate-nitrogen (NO3–-N), ammonium nitrogen (NH4+-N), total phosphorus (TP), available phosphorus (AP), total potassium (TK), and available potassium (AK)) and how they vary with environmental factors in the Chinese Loess Plateau. During the growing season, we collected 540 soil samples from the 0 to 100 cm soil layer across five major land-use types, different slope aspects, and varying altitudes. Additionally, a meta-analysis of literature data further corroborated the effective accumulation of soil nutrients through terracing in the Loess Plateau. Our findings are as follows: (1) Terraced fields, regardless of land-use type, showed a significant improvement in SOC and TN content. (2) Soil nutrient contents within terraced fields were predominantly higher on sunny slopes. (3) Terraces at lower altitudes are characterized by elevated SOC concentrations. (4) A meta-analysis of literature data pertaining to terracing and soil nutrients in this region confirmed the effective accumulation of soil nutrients through terracing. The elucidated outcomes of this study offer a profound theoretical underpinning for the accurate planning and management of terraces, the scientific utilization of land resources, and the enhancement of land productivity.